The Fall and Rise of the Concept of Uncertainty in the History of Economic Thought - Nofal, Sulafa (Brazilian Keynesian Review, 2023)
Uncertainty is one of these central concepts towards which economists have formed diverse and contradictory views. Traditionally, mainstream economists ignore the fundamental role of uncertainty and fully embrace individual rationality. This related to the closed-system ontology adopted by them, whereby uncertainty is viewed as a source of disturbance and treated as an external shock. But the financial and economic crises have reopened the debate about the consequences of such neglect. The article, in turn, is an attempt to tell the story of economic debates of uncertainty’s ups and downs. It resorts to the history of economic thought as an analytical tool to trace the evolution of the concept of uncertainty and the arguments presented by schools of economic thought, whether in defense or rejecting the centrality of this concept. Moreover, discussing uncertainty brought to the fore other related concepts such as ‘animal spirit’ and irrationality and thus paved the way for aspects recently addressed in the behavioral economics.